2022
DOI: 10.1111/trf.16950
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the risk of transfusion‐transmitted infections with vector‐borne agents solely by means of pathogen reduction

Abstract: Background: This study evaluated whether pathogen reduction technology (PRT) in plasma and platelets using amotosalen/ultraviolet A light (A/UVA) or in red blood cells using amustaline/glutathione (S-303/GSH) may be used as the sole mitigation strategy preventing transfusion-transmitted West Nile (WNV), dengue (DENV), Zika (ZIKV), and chikungunya (CHIKV) viral, and Babesia microti, Trypanosoma cruzi, and Plasmodium parasitic infections. Methods: Antibody (Ab) status and pathogen loads (copies/mL) were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In this sense, another limitation is that pre‐inactivation titres might not correlate with viremia in actual ongoing infections in volunteer donors. However, recently Stramer et al have shown viral titres in infected blood donors similar to those shown in studies using spiking techniques (West Nile virus 3.25 log 10 copies/ml, dengue virus 3.89 log 10 copies/ml, Zika virus 4.92 log10 copies/ml, Chikungunya virus 6.11 log 10 copies/ml) [20].…”
Section: Discussionmentioning
confidence: 68%
“…In this sense, another limitation is that pre‐inactivation titres might not correlate with viremia in actual ongoing infections in volunteer donors. However, recently Stramer et al have shown viral titres in infected blood donors similar to those shown in studies using spiking techniques (West Nile virus 3.25 log 10 copies/ml, dengue virus 3.89 log 10 copies/ml, Zika virus 4.92 log10 copies/ml, Chikungunya virus 6.11 log 10 copies/ml) [20].…”
Section: Discussionmentioning
confidence: 68%
“…The highest VLs in seronegative blood donors during the epidemic approached 10 8 IU RNA/ml, 23 with 2% (4 out of 209) of Puerto Rican ZIKV RNA reactive/seronegative donors identified in 2016/2017 having viral loads above 10 7 IU 9 . Using an average of the in vitro infectivity to VL ratio for our three human plasmas (183 IU RNA/PFU), ~10 8 IU of ZIKV RNA would equate to ~5 × 10 5 PFU/ml although in the current and previous 14 studies, it is important to note that RNA/PFU ratios are not consistent over the course of acute infection.…”
Section: Discussionmentioning
confidence: 95%
“…Such risk may be further mitigated by applying PR technology. In addition, applying PR to platelets in the setting of arboviruses outbreaks, notably those associated with a transfusion risk such as West Nile virus [14], allows for an immediately available alternative to specific testing or targeted donor deferral [15].…”
Section: Discussionmentioning
confidence: 99%